Improve Professionalism with Matra Health Optimization Soldier of the Health Corps in Lakeslain to Support Navy Duty - Indra Widjayanto; Victor Pardamean (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In realizing this policy, strategies are needed, namely Strategy 1 Realizing an increase in human resources through increasing quantity and quality in order to increase the professionalism of the health corps soldiers in Lakesla in order to support the tasks of the Navy. This can be done by means of submitting a request to increase the number of personnel to the Kadisminpersal and Kadiskesal. Coordinate as an effort to oversee the application letter. Lakesla creates Monthly Personnel Report with real data. Maintain good communication with Aspers Kasal, Kadiskesal and Kadisminpersal. The Indonesian Navy opened training and development courses for Lakesla soldiers, as well as improving the quality of human resources through seminars. Strategy 2 Realizing an increase in facilities and infrastructure through procurement to increase the professionalism of the health corps soldiers in Lakesla in order to support the tasks of the Navy. This can be done through efforts, namely submitting applications for facility support in stages, coordinating with local local governments in the context of procuring facilities and infrastructure, both in the form of borrowed goods and grants, coordinating with companies in the context of procuring facilities and infrastructure, both in the form of borrowed goods and grants. Strategy 3 Realizing an increase in binding regulations to be better in order to increase the professionalism of the health corps soldiers in Lakesla in order to support the tasks of the Navy. This can be done by means of the Headquarters issuing a telegram about the importance of eye health, Diskesal issuing a regulation on the importance of improving the health of the dimension. Lakesla made a consignment so that equipment operators must be certified. Lakesla made consignments regarding the operation of existing equipment.